2d solar thermal direct absorption comparison between gold and silver nanoparticle - Abdul-Mubarak Yussif Yidana (Renewable Energy and Sustainable Development, 2023)
In recent years, the application of nanoparticles for direct thermal absorption in solar energy technology has emerged as a transformative advancement, showing significant potential compared to traditional solar collectors. In this research, nanofluids containing silver and gold nanoparticles were simulated, using water and ethylene glycol as the base fluid. The simulations were carried out using a modelled rectangular test cell, employing constant heat flux conditions through the ANSYS Fluent software. This study builds upon prior research by extending the comprehension of how nanofluids, particularly those involving silver and gold nanoparticles, can enhance photothermal absorption rates. The primary objective of this paper is to conduct a comparative analysis of the photothermal absorption rates exhibited by the two nanofluids under two simulation cases: (1) a constant heat flux applied to only one side of the wall and (2) a constant heat flux applied to both sides of the wall. The results show that both silver and gold nanofluids have excellent photothermal absorption rate and increase significantly when heat flux is applied to both sides of the wall. A better performance is observed for silver ethylene glycol-based nanofluid. Therefore, for a more photothermal absorption rate, it is recommended that silver ethylene glycol based nanofluid should be used.   Received: 06 May 2023 Accepted:23 September 2023 Published: 30 October 2023